How to Explain CouchSurfing’s Success? - Dén-Nagy, Ildikó; Király, Gábor (Szociológiai Szemle, 2023)
In this paper we describe the social network of CouchSurfing as an innovative, non-monetary model for the traditional international hospitality and travel market. This paper is written to describe our understanding of how it can operate and expand in spite of potential risks and uncertainties. We present the results of an exploratory qualitative research project that was conducted in Hungary in 2012/13. The findings indicate that: (1) a high level of trust as a personality trait characterizes members; (2) trust can be interpreted as a strong cultural rule; (3) members perceive a low level of risk and have limited practical knowledge about the safety features of the system; and (4) trust towards a given member is not based on rational calculation but on emotions.